Sex Differences in IL-33-Induced STAT6-Dependent Type 2 Airway Inflammation - Zhao, Hedi; Moarbes, Vanessa; Gaudreault, Véronique; Shan, Jichuan; Aldossary, Haya; Cyr, Louis; Fixman, Elizabeth D. (Frontiers in Immunology, 2019)
Sex differences in asthma prevalence are well documented but poorly understood. Murine models have contributed to our understanding of mechanisms that could regulate this sex disparity, though the majority of these studies have examined responses present after Th2 adaptive immunity is established. We have now investigated how sex influences acute activation of innate cell populations in the lung upon initial exposure to the model antigen, ovalbumin (OVA), in the presence of IL-33 (OVA+IL-33), to prime the lungs for type 2 immunity. We also examined how inflammatory responses induced by OVA+IL-33 were altered in mice lacking the STAT6 transcription factor, which is activated by IL-13, an effector cytokine of IL-33. Our data demonstrate that type 2 inflammation induced by OVA+IL-33 was more severe in female mice compared to males. Females exhibited greater cytokine and chemokine production, eosinophil influx and activation, macrophage polarization to the alternatively activated phenotype, and expansion of group 2 innate lymphoid cells (ILC2s). While increases in ILC2s and eosinophils were largely independent of STAT6 in both males and females, many other responses were STAT6-dependent only in female mice. Our findings indicate that a subset of type 2 inflammatory responses induced by OVA+IL-33 require STAT6 in both males and females and that enhanced type 2 inflammation in females, compared to males, is associated with greater IL-13 protein production. Our findings suggest blunted IL-13 production in males may protect against type 2 inflammation initiated by OVA+IL-33 delivery to the lung.